3D CFD simulation of aerodynamics of a 406 MW[t] CFB boiler; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Koksharev O. M. Oleg (2017, 2017)
Title screen